Distributed antenna systems aspects and deployment - Huq, K.S. (2012)
A lot of schemes are proposed to exploit the transmit diversity. Distributed antenna systems (DAS) constitute one of the most attractive schemes to efficiently achieve the stringent quality of service demands of next generation wireless networks. In this paper, we investigated MISO assisted different transmission techniques used in DAS and the performance of downlink multi-cell DAS in terms of capacity improvement using SINR for different transmission scheme. A system level simulation tool is used to analyze the performance.